TOURIST COMMUNICATION: A SPECIALIZED DISCOURSE WITH DIFFICULTIES IN TRANSLATION - Merkaj, Ledina (European Scientific Journal, ESJ, 2014)
In everyday speech, we often hear expressions like language of music, language of computing, language of civil engineering etc., and we know that these various fields communicate with us. Why should we not use this term: the language of tourism? This article highlights the importance of considering and developing the language of tourism as a specialized discourse which encounters several difficulties in translation. It is language-like in its properties; it is structured, it follows certain grammar rules, it has a specialized vocabulary and a semantic content, it conveys messages and operates through a conventional system of symbols and codes; moreover, it adopts a special register. As tourism communication is an interculture discourse not only should the translator be proficient in both languages, but s/he should also be multicultural and able to identify with the original author as well as with the content in order to detect all the finer points of the language s/he is translating into. The major problem in translating tourist discourse is due to its cultural content. This type of texts describes and informs about other cultures and therefore, their main difficulty is to introduce a reality (being a city, a country, a type of food, etc.) to a person who may have never heard of it. Also, we often find words or concepts that do not exist in other cultures, so called realia, what makes translators employ different techniques with the aim at transfering the original meaning to the target audience and to solve the problem.